Provision of community pharmacy services during COVID-19 pandemic: a cross sectional study of community pharmacists’ experiences with preventative measures and sources of information - Kreshnik Hoti; Arianit Jakupi; Dardan Hetemi; Denis Raka; Jeff Hughes; Shane P. Desselle (2020)
Background An infectious disease caused by a novel coronavirus (later called COVID-19) reached pandemic levels in 2020 and community pharmacists were involved in responding to this pandemic, also in Kosovo. Objectives To explore the experiences of community pharmacists in relation to provision of community pharmacy services during COVID-19 pandemic. Setting Community pharmacists in Kosovo. Methods This was a cross-sectional study where data was collected via a self-administered online questionnaire, from 264 pharmacists actively practicing in Kosovo during the pandemic. The questionnaire consisted of a combination of closed and open-ended questions, optional statements and statements on a five-point Likert scale, derived at least in part from the Transtheoretical Model. One-way analysis of variance was used to analyze differences in responses to Likert-type items whereas categorical variables were analyzed using Chi square testing. Main outcome measures Community pharmacists' perceptions on COVID-19 related preventative measures. Results A response rate of 40.6% was achieved. Sufficient and adequate COVID-19-related preventative measures were being implemented by a majority of pharmacies (n = 232; 87.9%), and over two-thirds of respondents agreed/strongly agreed that their pharmacies were sufficiently prepared with protective equipment for their personnel. Implementation of preventative measures was associated with respondents' perception that pharmacists and the pharmacy profession were valued more by patients during the pandemic and to a lesser degree, by other health professionals. Most commonly stated pros dealt with employee and patient safety, while key cons dealt with increased costs and running out of the necessary protective equipment. Key barriers to pharmacy activities were price increases by wholesalers, and patients' panic and excessive buying, whereas drivers dealt with professional obligation to assist and opportunity to prove inseparable to other health professionals. The most popular means of accessing COVID-19 related information by pharmacists was via mobile devices and information from professional organizations was considered most useful by pharmacists. Conclusions Community pharmacies actively implemented various measures as precautions to mitigate the spread of COVID-19. Our findings highlight the value of continuous provision of information by professional organizations and use of mobile devices as key means to access information by pharmacists.